Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get detailed and accurate answers to your questions from a community of experts on our comprehensive Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
To solve the equation [tex]\(||x - 1| - 2| = |x - 3|\)[/tex], we need to consider the behaviors of the absolute value functions within the equation. The absolute value function splits into different cases based on the ranges of input values, so we need to evaluate all possible cases.
### Step-by-Step Solution
1. Break down the absolute values:
The equation is [tex]\(||x - 1| - 2| = |x - 3|\)[/tex]. We start by analyzing the inner absolute value function [tex]\(|x - 1|\)[/tex]:
- Case 1: [tex]\(x \geq 1\)[/tex]
[tex]\[ |x - 1| = x - 1 \][/tex]
- Case 2: [tex]\(x < 1\)[/tex]
[tex]\[ |x - 1| = 1 - x \][/tex]
2. Substitute the cases into the equation [tex]\(||x - 1| - 2| = |x - 3|\)[/tex]:
- For [tex]\(x \geq 1\)[/tex]:
[tex]\[ |x - 1| = x - 1 \][/tex]
Substituting this into the original equation, we get:
[tex]\[ ||x - 1| - 2| = |x - 3| \][/tex]
Which simplifies to:
[tex]\[ |(x - 1) - 2| = |x - 3| \][/tex]
Thus:
[tex]\[ |x - 3| = |x - 3| \][/tex]
This is true for all [tex]\(x \geq 1\)[/tex].
- For [tex]\(x < 1\)[/tex]:
[tex]\[ |x - 1| = 1 - x \][/tex]
Substituting this into the original equation, we get:
[tex]\[ ||1 - x| - 2| = |x - 3| \][/tex]
Which simplifies to:
[tex]\[ |(1 - x) - 2| = |x - 3| \][/tex]
Thus:
[tex]\[ |1 - x - 2| = |x - 3| \][/tex]
Simplifying inside the absolute value:
[tex]\[ |1 - x - 2| = |x - 3| \][/tex]
Simplifies to:
[tex]\[ |-(x + 1)| = |x - 3| \][/tex]
Simplifies further to:
[tex]\[ |x + 1| = |x - 3| \][/tex]
3. Break the resulting absolute values into additional cases:
[tex]\[ |x + 1| = |x - 3| \][/tex]
- Case A: [tex]\(x + 1 = x - 3\)[/tex]
[tex]\[ 1 = -3 \][/tex]
This is a contradiction and has no solution.
- Case B: [tex]\(x + 1 = -(x - 3)\)[/tex]
[tex]\[ x + 1 = -x + 3 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x + x = 3 - 1 \][/tex]
[tex]\[ 2x = 2 \][/tex]
[tex]\[ x = 1 \][/tex]
- Case C: [tex]\(x \geq 1\)[/tex]
As previously established, [tex]\(|x - 3| = |x - 3|\)[/tex] is always true.
Combining all these results, we see that when verifying back into the original equation, [tex]\(x = 1\)[/tex] was already covered under the condition [tex]\(x \geq 1\)[/tex].
Therefore, the solutions to the given equation are:
### Solution:
[tex]\[ x \geq 1 \][/tex]
To summarize, the step-by-step approach yielded that valid solution based on analyzing cases of absolute values. Solving [tex]\(||x - 1| - 2| = |x - 3|\)[/tex] confirms that [tex]\(x \geq 1\)[/tex].
### Step-by-Step Solution
1. Break down the absolute values:
The equation is [tex]\(||x - 1| - 2| = |x - 3|\)[/tex]. We start by analyzing the inner absolute value function [tex]\(|x - 1|\)[/tex]:
- Case 1: [tex]\(x \geq 1\)[/tex]
[tex]\[ |x - 1| = x - 1 \][/tex]
- Case 2: [tex]\(x < 1\)[/tex]
[tex]\[ |x - 1| = 1 - x \][/tex]
2. Substitute the cases into the equation [tex]\(||x - 1| - 2| = |x - 3|\)[/tex]:
- For [tex]\(x \geq 1\)[/tex]:
[tex]\[ |x - 1| = x - 1 \][/tex]
Substituting this into the original equation, we get:
[tex]\[ ||x - 1| - 2| = |x - 3| \][/tex]
Which simplifies to:
[tex]\[ |(x - 1) - 2| = |x - 3| \][/tex]
Thus:
[tex]\[ |x - 3| = |x - 3| \][/tex]
This is true for all [tex]\(x \geq 1\)[/tex].
- For [tex]\(x < 1\)[/tex]:
[tex]\[ |x - 1| = 1 - x \][/tex]
Substituting this into the original equation, we get:
[tex]\[ ||1 - x| - 2| = |x - 3| \][/tex]
Which simplifies to:
[tex]\[ |(1 - x) - 2| = |x - 3| \][/tex]
Thus:
[tex]\[ |1 - x - 2| = |x - 3| \][/tex]
Simplifying inside the absolute value:
[tex]\[ |1 - x - 2| = |x - 3| \][/tex]
Simplifies to:
[tex]\[ |-(x + 1)| = |x - 3| \][/tex]
Simplifies further to:
[tex]\[ |x + 1| = |x - 3| \][/tex]
3. Break the resulting absolute values into additional cases:
[tex]\[ |x + 1| = |x - 3| \][/tex]
- Case A: [tex]\(x + 1 = x - 3\)[/tex]
[tex]\[ 1 = -3 \][/tex]
This is a contradiction and has no solution.
- Case B: [tex]\(x + 1 = -(x - 3)\)[/tex]
[tex]\[ x + 1 = -x + 3 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x + x = 3 - 1 \][/tex]
[tex]\[ 2x = 2 \][/tex]
[tex]\[ x = 1 \][/tex]
- Case C: [tex]\(x \geq 1\)[/tex]
As previously established, [tex]\(|x - 3| = |x - 3|\)[/tex] is always true.
Combining all these results, we see that when verifying back into the original equation, [tex]\(x = 1\)[/tex] was already covered under the condition [tex]\(x \geq 1\)[/tex].
Therefore, the solutions to the given equation are:
### Solution:
[tex]\[ x \geq 1 \][/tex]
To summarize, the step-by-step approach yielded that valid solution based on analyzing cases of absolute values. Solving [tex]\(||x - 1| - 2| = |x - 3|\)[/tex] confirms that [tex]\(x \geq 1\)[/tex].
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.